Evolution of Seismicity During a Stalled Episode of Reawakening at Cayambe Volcano, Ecuador - Butcher, S.; Bell, A. F.; Hernandez, S.; Ruiz, M. (Frontiers in Earth Science, 2021)
Cayambe Volcano, is an ice-capped, 5790m high, andesitic-dacitic volcanic complex, located on the equator in the Eastern Cordillera of the Ecuadorian Andes. An eruption at Cayambe would pose considerable hazards to surrounding communities and a nationally significant agricultural industry. Although the only historically documented eruption was in 1785, it remains persistently restless and long-period (LP) seismicity has been consistently observed at the volcano for over 10 years. However, the sparse monitoring network, and complex interactions between the magmatic, hydrothermal, glacial, and tectonic systems, makes unrest at Cayambe challenging to interpret. In June 2016 a seismic `crisis’ began at Cayambe, as rates of high frequency volcano-tectonic (VT) earthquakes increased to hundreds of events per day, leading to speculation about the possibility of a forthcoming eruption. The crisis began two months after the M$_{w}$7.8 Pedernales earthquake, which occurred on the coast, 200 km from Cayambe. Here we show that the 2016 seismicity at Cayambe resulted from four distinct source processes. Cross correlation, template matching, and spectral analysis isolate two source regions for VT earthquakes - tectonic events from a regional fault system and more heterogeneous VTs from beneath the volcanic cone. The temporal evolution of the LP seismicity, and mean Q value of 9.9, indicate that these events are most likely generated by flow of hydrothermal fluids. These observations are consistent with a model where a new pulse of magma ascent initially stresses regional tectonic faults, and subsequently drives elevated VT seismicity in the edifice. We draw comparisons from models of tectonic-volcanic interactions, and speculate that static stress changes from the Pedernales earthquake would put Cayambe volcano in an area of dilation, providing a mechanism for magma ascent. They provide a better understanding of `background’ seismicity at Cayambe allowing faster characterization of future crises, and a benchmark to measure changes driven by rapid glacial retreat.